Theranos, Inc. : managing risk in a high-flying biotech start-up - Kelley, Caitlin (SAGE Knowledge. Cases., 2017)
The case describes how a start-up bio-tech company covered up failed quality control standards leading to an expose in the Wall Street Journal. The study examines the effects of this scandal both on the value of Theranos and its ability to continue manufacturing medical supplies.